Susceptibility of Leptocybe invasa (Hymenoptera: Eulophidae) to insecticides in greenhouse - Luna-Cruz, Alfonso; Vanegas-Rico, Juan Manuel; Rodríguez-Leyva, Esteban; Lomeli-Flores, J. Refugio (Instituto de Ecología, A.C., 2020)
The eucalyptus gall wasp Leptocybe invasa, is an Australian native pest that affects plantations of Eucalyptus spp. E. camaldulensis is the most susceptible host; worldwide it is used for sawn wood and pulp or used as urban tree in many Mexican cities. The exotic nature of L. invasa and its development in galls, impedes its natural regulation for native entomophagous in Mexico, which represents a threat for the producing regions of eucalyptus and urban areas. Thus, the present study evaluated the efficiency of insecticides in greenhouse conditions, by means of soil and foliar applications, on the immature stages: egg, young larva, mature larva and pupa, using plants of E. camaldulensis less than one year old. Major mortality was registered in egg (35% to 79%) and young larva (40% to 75%) when Carbofuran or Imidacloprid was applied to the soil. The efficiency of these products diminished (mortality < 5%) in the stages of mature larva and pupa. The application of Spirotetramat stood out in the application on leaves, but it is not enough on its own to control the plague (mortality < 40%). Based on the results of this investigation, and previous studies published in the specialized literature, it is suggested that chemical management on L. invasa in greenhouses is feasible but only as an emergency measure. This, using Carbofuran or Imidacloprid in application to the soil, alternating with an application on the leaves after Spirotetramat.